If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3y + 5 = 8 + 2y Reorder the terms: 5 + 3y = 8 + 2y Solving 5 + 3y = 8 + 2y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-2y' to each side of the equation. 5 + 3y + -2y = 8 + 2y + -2y Combine like terms: 3y + -2y = 1y 5 + 1y = 8 + 2y + -2y Combine like terms: 2y + -2y = 0 5 + 1y = 8 + 0 5 + 1y = 8 Add '-5' to each side of the equation. 5 + -5 + 1y = 8 + -5 Combine like terms: 5 + -5 = 0 0 + 1y = 8 + -5 1y = 8 + -5 Combine like terms: 8 + -5 = 3 1y = 3 Divide each side by '1'. y = 3 Simplifying y = 3
| 7+3(s-2t)= | | 3x-5x+4=8 | | 7+2(s-3t)= | | (4v-5)(3v+1)=8v^2-32v-32 | | 13x+14=326 | | (x+5)(x+5)=22x-11 | | 11x^2-10x=0 | | 230-5x=31x+18 | | x^4+11x^2=900 | | 9(6x-3)=90x | | 2+58=8-10 | | 8-9x=168-37x | | 13=r+2 | | 85-6x=12x+15 | | .8571x-.4285=7 | | 5x=3x-12 | | 2x-6x=4 | | 14-7x=124-42x | | -153-7x=10x-17 | | .833x+.1818=1.166x | | 38-6x=3x+18 | | 9p+2=7+8p | | 3x+11=-88-8x | | 8-8x=40-36x | | 169-6x=6x+13 | | 8x+3x=2x+45 | | 66-2x=11-10x | | .33x-18=x-6 | | 3z/5=5 | | 244-5x=40x+24 | | 7x-6=4x+7x+12 | | 4x+7=-97-9x |